Legal Awareness of Traditional Medicine Microbusinesses Regarding Halal Certificate Ownership in Bojonegoro Regency - Ibrahim Musthofa; Eny Sulistyowati; Kiki Cahya Muslimah (Universitas Negeri Surabaya, 2025)
This study aims to examine the legal awareness of traditional medicine micro-business sellers in Bojonegoro Regency regarding halal certification and to identify the factors influencing this awareness. The research was motivated by the fact that many traditional medicine micro-business actors in the region have not registered their products with the Halal Product Assurance Agency (BPJPH), despite the growing importance of halal certification in consumer protection and market access. The research adopts an empirical legal method with two central problems: (1) the level of legal awareness among traditional herbal medicine sellers concerning halal certificates, and (2) the internal and external factors influencing this awareness. The study reveals that legal awareness in this sector remains relatively low, as reflected in four key indicators: legal knowledge, legal understanding, legal attitudes, and patterns of legal behavior. Contributing factors include internal aspects such as limited educational background and lack of access to legal information, as well as external influences such as weak regulatory enforcement and insufficient socialization by relevant authorities. Based on these findings, the study recommends intensified outreach and education programs targeting traditional medicine sellers, as well as policy interventions to simplify the halal certification process for micro businesses. Strengthening collaboration between BPJPH, local government, and community leaders is also essential to enhance legal compliance and promote the legitimacy and competitiveness of traditional medicine in the halal market.